The Impact of Strategic Leadership Practices on Organizational performance: A Field Study at Yemeni Private Hospitals in Sana’a - Abdu Sallam, Fahmi Mohammed; Alhakimi, Wail Sultan (University of Science and Technology Journal for Management and Human Sciences, 2023)
The study aimed to explore the impact of strategic leadership and its dimensions (strategic direction, core capabilities, human capital development, organizational culture, and balanced organizational control) on organizational performance in Yemeni private hospitals in Sana’a. The study followed the descriptive quantitative design. The study population consisted of seven Yemeni private hospitals in Sana’a selected based on their size and age. The study used the complete census method to select the study sample which included 270 individuals with leadership and supervisory positions. A total of 270 questionnaires were distributed, of which 264 were returned. Only 244 questionnaires were valid for analysis. Data was analyzed using SPSS 28 software. The study revealed that there is a statistically significant impact of strategic leadership and its dimensions (strategic direction, core capabilities, human capital development, organizational culture, and balanced organizational control) on organizational performance in Yemeni private hospitals in Sana’a. The study recommends paying more attention to strategic leadership in hospitals, training staff, establishing an organizational culture enhanced by ethical practices, and adopting a control system to correct errors and improve the quality of service.